Agglomeration, Segmentation and Technology Choice - yukiko sawada (European Regional Science Association (ERSA), 2014)
This paper presents a simple two country model in which firms in manufacturing sector choose a technology level (high or low). I show how trade integration and productivity differential affect technology choice clearly. In particular, if the gap of productivity of high technology is medium, firms locating in country employ high technology and other firms in developing country do low technology. In this case, increasing productivity of high technology makes the welfare level of a consumer in low technology country decrease.
Keywords: F10; F12; 330